After Decades of Suburban Deer Research and Management in the Eastern United States: Where Do We Go From Here? - Paul D. Curtis (Human-Wildlife Interactions, 2020)
State wildlife agencies have regulatory authority and oversight over deer (Cervidae) management in the United States. However, increased urban sprawl and overabundant deer populations have created increased human–deer conflicts. Because of the growing controversy surrounding the use of traditional management practices such as regulated hunting in suburban areas in the eastern United States, managers are now using specialized tools and management approaches to reduce deer conflicts in urban areas. However, this has created new challenges as they try to meet the desires of diverse stakeholder groups. Although deer management programs in urban areas differ somewhat in every state, effective management options remain limited. Essentially the same management tools that were used for 3 decades have not changed, even with substantial investments in deer research. Despite public support for deer fertility control, it is still largely experimental and expensive. Immunocontraceptive vaccines are seldom used because of the cost and difficulty of retreating free-ranging deer. Surgical sterilization of deer has shown promise, but the scale of application remains limited by cost and the number of deer that need to be handled. Lethal deer removal remains the only method that has consistently reduced deer numbers in an acceptable time frame at multiple scales. Even in areas where urban deer numbers have been substantially reduced using lethal methods, the resulting effects on deer populations and human–deer conflicts have been poorly documented. In highly fragmented, developed landscapes, removing enough deer to demonstrate impact reduction has been a difficult and expensive process. It usually takes multiple approaches across several years to achieve desired results. Thus, the lack of long-term planning and sufficient budgets needed to sustain management efforts may impede overall program success and sustainability. Herein, I review the lessons learned from multiple deer research and management efforts from suburban areas in the eastern United States and highlight potential directions for future urban deer management programs.